Cooling the neck region during exercise in the heat - Tyler, C. J.; Sunderland, C. (Journal of Athletic Training, 2011)
Context: Cooling the neck region can improve the ability to exercise in a hot environment. It might improve performance by dampening the perceived level of thermal strain, allowing individuals to override inhibitory signals.